Answer:
see explanation
Explanation:
Given
2x² + 7x = 15 ( subtract 15 from both sides )
2x² + 7x - 15 = 0 ← in standard form
To factorise the left side
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 × - 15 = - 30 and sum = + 7
The factors are + 10 and - 3
Use these factors to split the x- term
2x² + 10x - 3x - 15 ( factor the first/second and third/fourth terms )
2x(x + 5) - 3(x + 5) ← factor out (x + 5) from each term
(x + 5)(2x - 3) ← in factored form